Pengaruh Influencer Sosial Media Terhadap Keputusan Pembelian Produk Yang Dipromosikan - Syafril, Syafril; Mohdari, Mohdari; Fahmi, Muhamad; Fadilah, Neti Rosiana (JURNAL ADMINISTRASI & MANAJEMEN, 2025)
This study aims to determine the influence of social media influencers on purchasing decisions for promoted products. This study uses a Google form as a medium distributed to respondents online. The research sample consisted of 108 people who were members of the WhatsUp group owned by the researcher from various campuses and areas where the respondents came from. The sampling technique used in this study is random sampling, which is a sampling technique based on population members who happen to be met and are willing to be respondents. This study is a quantitative descriptive study, which is a research method based on the philosophy of positivism, which is used to study certain populations or samples. Judging from its purpose, this study is included in hypothesis testing research. A hypothesis is a temporary answer to a research problem whose truth still needs to be tested. Data testing was carried out using SPSS 26 with the classical assumption test and the t-test with simple linear regression. The results of this study indicate that there is a significant influence and positive correlation between the Social Media Influencer variable and the Purchase Decision for Promoted Products. Keywords: Influencer, Social Media, Product Purchase, Quantitative Descriptive, Respondents